Role of HR in Corporate Renewal - Szumowski, Witold (Rola działu HR w procesie odnowy przedsiębiorstwa, 2010)
The author of the paper attempts to determine the scope in which HR service participates in the process of corporate development and renewal. The author points to two key areas in which HR should support the corporations. With reference to these two areas (strategic partnership and change management), the author presents the results of the empirical research.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 148, s. 153-163
Keywords: HR; corporate renewal; new HR service's way of operating; change management; strategic HR